WEB SURFING AMONG UNIVERSITY STUDENTS IN ANAMBRA STATE, NIGERIA: IMPLICATION FOR SCHOOL WORK ENGAGEMENT - Chukwuebuka Ikechukwu, Chigbo (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Numerous reports indicate that the student population is likely vulnerable to the challenges associated with increased internet activity. The paper presents the findings on the role of web surfing on schoolwork engagement based on observation of university students in Anambra State, Nigeria. Two hundred thirty-two undergraduates enrolled in different courses in five tertiary institutions in Anambra State were conveniently recruited for the study. They completed a self-report measure of the Schoolwork Engagement Inventory and Smartphone Addiction Scale-Short Version (SAS-SV). The simple regression analysis conducted on the data revealed that internet dependency statistically significantly predicted the respondent's schoolwork participation F (1,230), 42.53, P<.000. Thus, the result affirmed the hypothesis that web surfing predicts schoolwork engagement in undergraduates. The practical implications and recommendations are discussed.